2011
DOI: 10.1016/j.jtbi.2011.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic theory of protein synthesis and polysome: Ribosome profile on a single mRNA transcript

Abstract: The process of polymerizing a protein by a ribosome, using a messenger RNA (mRNA) as the corresponding template, is called translation. Ribosome may be regarded as a molecular motor for which the mRNA template serves also as the track. Often several ribosomes may translate the same (mRNA) simultaneously. The ribosomes bound simultaneously to a single mRNA transcript are the members of a polyribosome (or, simply, polysome). Experimentally measured polysome profile gives the distribution of polysome sizes. Recen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…If motion is allowed only in one direction then ASEP is sometimes called the totally asymmetric simple exclusion process (TASEP). ASEP (and its many variants) is regarded as a paradigmatic model for non-equilibrium statistical mechanics and has been used to model and analyze various biological systems and processes, including intracellular transport, molecular motors, pedestrian dynamics and of course gene expression [75][80].…”
Section: Preliminaries: From Asep To the Rfmmentioning
confidence: 99%
“…If motion is allowed only in one direction then ASEP is sometimes called the totally asymmetric simple exclusion process (TASEP). ASEP (and its many variants) is regarded as a paradigmatic model for non-equilibrium statistical mechanics and has been used to model and analyze various biological systems and processes, including intracellular transport, molecular motors, pedestrian dynamics and of course gene expression [75][80].…”
Section: Preliminaries: From Asep To the Rfmmentioning
confidence: 99%
“…Moreover, these basic TASEP models neither incorporate any mechanism for specifically selecting the correct amino acid monomer, nor do they allow for the possibility of translational error, etc. Therefore, such TASEP models are too simple to account for the effects of various mechano-chemical processes on the statistical properties of polysomes (58,72,111,130134). Finally, these models did not consider more complicated and global aspects of translation such as competition between mRNA molecules on ribosomes and translation factors, and between cognate and near-cognate tRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, these aspects can include, among others, the different conformational steps of the ribosome during one iteration of elongation (56,59,135136), the initiation itself includes various sub-steps (5′ end recognition, scanning, start codon recognition, etc) (55,137) that are usually not modeled in a rudimentary TASEP, the unfolding of the mRNA (61,138139), the diffusion of tRNA molecules (19,46,51,54,6162,66,69,131,134,140142), interactions between the nascent peptide and the ribosome (61,143144), diffusion of elongation factors (42), the addition of an amino acid to the growing polypeptide chain (5), tRNA molecule release (51), re-cycling of elongation factors (58,65,145), ribosome frame-shift (146), interactions between ribosomes and ribosome drop-off (46,5354,59,69,131,135,142), mRNA decay (70), and many additional aspects (Figure 1C). …”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies on the mechanisms of mRNA translation have been reported and draw on multiple approaches and tools such as experimental cell biology, bioinformatics, theoretical and computational biology, and recently systems and synthetic biology [2-9]. However, even though the fundamental mechanisms underlying mRNA translation are relatively clear, a number of detailed regulatory mechanisms are only now being uncovered, the full understanding of which will require an interplay between experiments and modelling.…”
Section: Introductionmentioning
confidence: 99%